The Shopping Motivation Analysis Of Nike Shoes Counterfeit Among STIE PGRI Dewantara Students - pancaningrum, erminati; Wardani, YA (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2019)
The purpose of this study is to find out and expand the shopping motivations that encourage consumers to use Nike shoes counterfeit products. This study uses descriptive research with quantitative survey research arch analysis techniques with a questionnaire as a data collection tool. The measurement scale used in this study is a Likert scale. Data analysis method used is descriptive analysis with SPSS for Windows. The results Showed that hedonic motivation predominates in encouraging consumers to buy and use the Nike shoe s counterfeit products Compared to the utilitarian motivation.